Intergenerational linkages in debt delinquency behaviors among young adults - Gan, Lena Su Yuin (Kansas State University, 2024)
This dissertation investigates the intergenerational factors that influence financial debt delinquency behaviors in young adulthood, focusing on the roles of parent-child relationships, parental socioeconomic status, individual attitudes, norms, and perceived financial control. Guided by the Theory of Planned Behavior (TPB) and Family Financial Socialization Theory (FFST), the study employs path analysis to explore how these variables mediate financial behaviors. Using data from the National Longitudinal Survey of Youth 1979 (NLSY79) and its Child and Young Adult Survey (NLSCYA), the research examines key pathways, including the mediating effects of risky attitudes, parental debt norms, and perceived financial control on the relationship between parental influences and debt delinquency. The findings reveal that while parental socioeconomic status and debt norms significantly affect young adults' financial behaviors, the influence of parent-child relationships on perceived financial control is more nuanced. Effect size analyses highlight the varying impact of different predictors, revealing that perceived financial control exerts a substantially greater influence on debt delinquency compared to other factors, emphasizing the importance of targeted interventions. The study underscores the importance of considering both direct and indirect effects in understanding financial socialization. Practical implications suggest that policymakers, financial educators, and practitioners should focus on enhancing perceived financial control and shaping healthy debt norms within families to mitigate financial delinquency. Future research should address the limitations of secondary data and further refine the measurement of constructs to capture the complex dynamics of financial behavior socialization.
Keywords: Intergeneration; Financial debt delinquency; Young adults; National Longitudinal Surveys (NLSY79) & (NLSCYA)